2022
DOI: 10.21203/rs.3.rs-2101028/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Construct validity of the COVID-19 Peritraumatic Distress Index (CPDI) in a Peruvian sample during COVID-19 lockdown and its relationship with anxiety and depression using structural equation modeling

Abstract: Background: The main aims of this study were to adapt the COVID-19 Peritraumatic Distress Index (CPDI) to the Peruvian population and to establish a model explaining depression using CPDI values and anxiety symptoms during the COVID-19 lockdown. Finally, we sought predictive values of the obtained CPDI factors for depression and anxiety as a secondary aim. Materials and Methods: An exploratory factor analysis (n = 300) was performed, followed by confirmatory factor analysis in a second phase (n = 1135). To ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Participants and procedure present study is a secondary analysis of two databases comprising online survey studies conducted in Peru and Spain during the COVID-19 pandemic. Certain ndings from this survey study have already been reported elsewhere 11,14 . The current study incorporates certain methodological aspects of both studies, primarily pertaining to the recruitment of participants, the description of the online survey, and the CPDI.…”
Section: Methodssupporting
confidence: 71%
See 4 more Smart Citations
“…Participants and procedure present study is a secondary analysis of two databases comprising online survey studies conducted in Peru and Spain during the COVID-19 pandemic. Certain ndings from this survey study have already been reported elsewhere 11,14 . The current study incorporates certain methodological aspects of both studies, primarily pertaining to the recruitment of participants, the description of the online survey, and the CPDI.…”
Section: Methodssupporting
confidence: 71%
“…However, since a correlation between the two factors was assumed, a principal component analysis with a promax rotation was performed in this study. Items 7, 8, and 11 were removed from the analysis 14 . When the datasets were combined and analyzed, the same number of factors and a similar distribution of items per factor were obtained (see Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations